Why Asset Administration Shells: A Survey on Uses and Challenges - Angelos Alexopoulos; Georgios Kalogeras; Konstantinos Koutras; Athanasios Kalogeras (IEEE Access, 2025)
In the cadre of the Industry 4.0 initiative, and its proposed RAMI 4.0 reference architecture, the Asset Administration Shell (AAS) is gaining traction in the industrial sector, ushering production practices to new precedents and enabling the incorporation of the latest digital technologies. However, the task of instigating the new era of industry is not without difficulties. The current work performs a systematic literature review of AAS by thoroughly reviewing 86 recently published journal articles. The aim is to put in scope current use cases of the AAS, categorise them and, thus, paint a comprehensive picture of AAS usage, by synthesizing all recent journal literature. The second part of the work focuses on highlighting current challenges that appear at the intersection of AAS with necessities of the industrial sector, as well as with the AAS’s integration with novel concepts and technologies.